1989
DOI: 10.1007/bf03179561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold storage of newly hatched larvae on survival rate, growth and egg production in silkwormBombyx mori L.

Abstract: Effects of refrigeration (5 ± I'C) of newly hatchet! silkworm larvae on survival rate, growth and egg production were studied in two multivoltine races, Pure Mysore and Hosa Mysore. When refrigerated for 10 days, moth emergence (males: 83·3% vs 89·4% and females: 92% vs 90'2%) and fecundity (465'5 vs 458'3) did not differ significantly from the control. Reductions in cocoon weight by 4% (1,323 g vs 1·271 g) and 10·7% (1'323 g vs 1·181 g) were caused by 5 and 10 days of refrigeration. Marked increase in early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Refrigeration is a method for modification of the life cycle widely used in the cultivation of silkworms. Benchamin et al (1989) reported that refrigeration of newly hatched larvae affected the survival rate, growth, and egg production of Bombyx mori. Refrigeration of cocoons also affected the fecundity and egg hatchability of B. mori (Gaurav et al 2015;Upadhyay et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Refrigeration is a method for modification of the life cycle widely used in the cultivation of silkworms. Benchamin et al (1989) reported that refrigeration of newly hatched larvae affected the survival rate, growth, and egg production of Bombyx mori. Refrigeration of cocoons also affected the fecundity and egg hatchability of B. mori (Gaurav et al 2015;Upadhyay et al 2006).…”
Section: Introductionmentioning
confidence: 99%